The Real Time Implementation of a Chaotic System's Synchronization for Secure Communication - Guler, Hasan; Celik, Vedat; Kaya, Turgay; Erol, Yavuz (Univ Osijek, Tech Fac, 2018)
The chaotic systems are preferred in secure communication systems as well as used in many different implementation areas Real time chaos synchronization is also required for secure communication systems In this study, the Master-Slave synchronization of chaotic Chen system was performed on a real time implementation for the secure communication systems Active control method was used in the design of controller required for the realization of synchronization The successful realization of the Master-Slave synchronization of the Chen system by using the controller designed on MATLAB/Simulink was shown by the obtained simulation results Moreover, by using analogue outputs of NI-DAQ card, the Master-Slave synchronization of the Chen system was obtained and secure communication was achieved on a real time basis under LabVIEW environment.
Keywords: active control; chaotic Chen system; Master-Slave synchronization; secure communication; LabVIEW